Mutations in the TaPIN1 peptidyl prolyl isomerase gene in Theileria annulata parasites isolated in Sudan. (December 2019) - Salim, Bashir; Chatanga, Elisha; Jannot, Guillaume; Mossaad, Ehab; Nakao, Ryo; Weitzman, Jonathan B.
Abstract: The tick-borne parasite Theileria annulata is the causative agent of tropical theileriosis or Mediterranean theileriosis. Infection of bovine leukocytes by the obligate intracellular parasites induces proliferative and invasive phenotypes associated with activated signaling pathways. The transformed phenotypes of infected cells are reversible by treatment with the theilericidal drug buparvaquone. Recent reports of resistance to buparvaquone in Africa and Asia highlight the need to investigate the mechanisms and prevalence of drug resistance. We screened 67 T. annulata isolates from Sudan to investigate mutations in the T. annulata prolyl isomerase I gene ( TaPIN1 ). The secreted TaPin1 interacts with host proteins to induce pathways driving oncogenic transformation and metabolic reprogramming. We found an Alanine-to-Proline mutation at position 53 (A53P) in the catalytic loop that was previously found in Tunisian drug-resistant samples. This is the first study reporting independent confirmation of the A53P mutation in geographically isolated samples. We found several additional mutations in the predicted N-terminal signal peptide that might affect TaPin1 processing or targeting. We found that many parasites also share mutations in both the TaPIN1 and the cytochrome b genes, suggesting that these two genes represent important biomarkers to follow the spread of resistance in Africa, the Middle East and Asia. Graphical abstract: Image 1